Aspectos da fisiopatologia da sepse em Piaractus mesopotamicus induzida por Aeromonas hydrophila - Claudiano, Gustavo da Silva [UNESP] (2015)
The pathogenesis of sepsis involves multiple interrelationships in the dynamics between various components related to the host and the pathogen, with high mortality rates in several animal species. Although it is a major cause of fish deaths, there is lack of literature about its physiopathology and the mechanisms of modulation. This work aimed to study the physiopathological aspects of the evolution of the septic response induced by Aeromonas hydrophila in Piaractus mesopotamicus - pacu. The dose was determined by the LD50 (LD50-96h) and estimated in 1,78 x 109. Sepsis was induced by the administration in the coelomic cavity and was followed by the collection of blood in the pre-determined times of 1, 3, 6, and 9 hours after induction and more control. There was a rapid increase of cortisol concentration in plasma, inhibition of glucose uptake, followed by hypocortisolemia and hyperglycemia. Thyroid hormones have immediate reduction of serum concentration of T3 and T4. The latter showed an increase after 6 HPI. Hormonal changes induced by sepsis-triggered changes in metabolic pathways enhancing protein and lipid catabolism, use of transient anaerobic glycolysis via and liver damage. The leucocyte count showed leukopenia and thrombopenia followed by cessation of leukocyte migration after 6 HPI and severe morphological changes in leukocytes and erythrocytes. The innate immune variables showed increased production of ROS after 3 HPI, followed by reduction without changing the concentration of serum lysozyme and progressive increase in SHA and ABA. After ip inoculation of A. hydrophila in pacu, clinical signs were evident of Aeromonas infection, growing bacteremia and survival of 57,14 % after 36 HPI